Effect of Octreotide on experimental corneal neovascularization - Demir, T; Çeliker, ÜO; Kükner, A; Mogulkoç, R; Çelebi, S; Çeliker, H (Scriptor Publisher, 1999)
Purpose:To examine the ability of subcutaneously administered Octreotide ( a long acting somatostatin analogue) to serve as an inhibitory agent for corneal neovascularization in eyes of Wistar Albino rats. Methods: Neovascular growth into the corneas of all the animals was induced by silver nitrate cauterization. Half of the animals which were randomly selected for the Octreotide group received 30 micrograms systemic Octreotide for 7 days. The treatment was initiated on the same day as chemical cauterization. The rest of the animals (control group) received no treatment. Slit lamp and histopathologic examination of the corneas of both groups were performed at the end of the study period. Results: It was observed that the corneal neovascularization and histopatologic scores of the Octreotide group were significantly lower than those of the control group (p<0.001, p<0.01). Conclusion: Systemic administration of Octreotide inhibits the corneal neovascular response in a rat model.
Keywords: Octreotide; corneal neovascularization; inflammation; rat